Nanotechnology applications in food : flavor, stability, nutrition and safety - Oprea, Alexandra Elena; Grumezescu, Alexandru Mihai (Academic Press, 2017)
Nanotechnology applications in food: flavor, stability, nutrition, and safety is an up-to-date, practical, applications-based reference that discusses the advantages and disadvantages of each application to help researchers, scientists, and bioengineers know what and what not to do to improve and facilitate the production of food ingredients and monitor food safety. The book offers a broad spectrum of topics trending in the food industry, such as pharmaceutical, biomedical, and antimicrobial approaches in food, highlighting current concerns regarding safety, regulations, and the restricted use of nanomaterials. Includes how nanobiosensors are useful for the detection of foodborne pathogens. - Resumé vydavatel
Keywords: potravinářství; potraviny; biotechnologie; nanotechnologie; nanobiotechnologie; food industry and trade; foodstuffs; biotechnology; nanobiotechnology; nanotechnology; kolektivní monografie; elektronické knihy; collective monographs; electronic books